2012
DOI: 10.1016/j.neuron.2012.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Medial Axis Shape Coding in Macaque Inferotemporal Cortex

Abstract: SUMMARY The basic, still unanswered question about visual object representation is this: what specific information is encoded by neural signals? Theorists have long predicted that neurons would encode medial axis or skeletal object shape, yet recent studies reveal instead neural coding of boundary or surface shape. Here, we addressed this theoretical/experimental disconnect, using adaptive shape sampling to demonstrate for the first time explicit coding of medial axis shape in high-level object cortex (macaque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
145
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(162 citation statements)
references
References 70 publications
(90 reference statements)
17
145
0
Order By: Relevance
“…We first briefly describe the 3D static shape features used by Hung et al [11] to represent the shape space in primate visual cortex. Since we are interested in moving 3D shapes, we represent a moving skeleton as a time-series of these 3D shape features and model the dynamics using a hierarchy of LDSs.…”
Section: Preliminariesmentioning
confidence: 99%
See 3 more Smart Citations
“…We first briefly describe the 3D static shape features used by Hung et al [11] to represent the shape space in primate visual cortex. Since we are interested in moving 3D shapes, we represent a moving skeleton as a time-series of these 3D shape features and model the dynamics using a hierarchy of LDSs.…”
Section: Preliminariesmentioning
confidence: 99%
“…In Yamane et al [28] and Hung et al [11], a 3D shape is very briefly shown, by using shading and disparity cues, to a macaque monkey with their head restrained so that they cannot move. The electrical activity of several neurons is then recorded.…”
Section: Shape Encoding In Primatesmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, previous studies on neural texture representation were typically based on strictly limited samples (6-8)-e.g., 15 different textures were used in Freeman et al (7)-despite a potentially large number of parameters describing the neural selectivity for various natural textures. In this study, we overcome this problem of dimensionality by combining the parametric texture synthesis with an adaptive sampling procedure (23)(24)(25) that efficiently sampled a portion of the stimuli that were expected to evoke stronger responses in the recorded neuron, as well as linear regression with a dimension-reduced version of the PS statistics. As a result, we successfully fitted neural responses to hundreds of textures using PS statistics.…”
mentioning
confidence: 99%